A classification of emotions study in software agent and robotics applications research - Subramainan L.; Yusoff M.Z.M.; Mahmoud M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Application programs; Computer aided instruction; Decision making; Digital libraries; Education computing; Intelligent agents; Intelligent vehicle highway systems; Multi agent systems; Robotics; Affective Component; Classification of emotions; Cognitive process; Emotion expression; Emotional agents; Intelligent tutoring system; Robotic applications; Robotics applications; Software agents